A randomized controlled trial of burping for the prevention of colic and regurgitation in healthy infants. (9th June 2014) - Kaur, R.; Bharti, B.; Saini, S. K.
Abstract Background Efficacy of burping in lowering colic and regurgitation episodes in healthy term babies lacks evidence in literature. Methods We conducted a randomized controlled trial to compare efficacy of burping versus no‐burping in 71 mother–baby dyads in community setting. Primary outcome was reduction in event rates of colic and regurgitation episodes over 3 months. Results Baseline characteristics were similar in two groups. Difference in incidence rates of colic between the control and burping group was 1.57 episodes/infant/100 weeks [95% confidence interval (CI): −0.63 to 3.76]. There was statistically no significant reduction in colic episodes between burping and non‐burping study subjects during 3 months of follow‐up (adjusted relative risk 0.64; 95% CI: 0.22–1.86, P‐value 0.41). Incidence rate difference of regurgitation episodes/infant/week between burping and control group was 4.36 (95% CI: 4.04 to 4.69) and there was statistically significant increase in burping group (adjusted relative risk 2.05; 95% CI: 1.92–2.18, P‐value < 0.0001). Conclusions Although burping is a rite of passage, our study showed that burping did not significantly lower colic events and there was significant increase in regurgitation episodes in healthy term infants up to 3 months of follow‐up.